Effects of different Pistacia species pollen on fruit dimension and weight in the Kirmizi variety - Ak B.E. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
In this experiment, the effects of P. vera, P. atlantica and P. terebinthus pollen on fruit dimensions and weight were investigated. The results were changed according to pollen sources. The fruit which were pollinated with P. vera pollen was better than other Pistacia species' pollen. Generally fruit weight, width and thickness were affected but length was not. Shelling percentage was also changed.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)